Online Simulation To Monitor Multiphase Flow Using Laser Source As Transmitter - Naizatul Shima Mohd Fadzil; Ruzairi Abdul Rahim; Mohd Hafiz Fazalul Rahiman; Siti Zarina Muji; Yasmin Abdul Wahab; Juliza Jamaludin (Elsevier, 2024)
Indexed by WOS/Scopus/ERA